Bridging education and industry: adapting secondary technical and vocational education (TVE) with regional economic development - Mohd Puad, Mohd Hazwan; Sheng, Haixia (Faculty of Educational Studies Universiti Putra Malaysia (UPM), 2024)
Educational funding is a critical factor influencing student outcomes. Secondary Technical and Vocational Education (TVE) is an important part of the Technical and Vocational Education(TVE) system , which directly serves local financial construction. This study aims to analyze the adaptability of regional economic construction and secondary technical and vocational education (TVE) development in Wuxi City, Jiangsu Province, China. The study utilized data from schools, companies, and government websites in Wuxi City and open-ended interviews with students, teachers, and workers from local enterprises. Participants were asked questions about the development of technical and vocational schools, the selection of the study program, and the recruitment of job seekers. The findings indicated that while secondary technical and vocational education (TVE) is not currently aligned with local and regional economic development in Wuxi City, there is significant potential for improvement. This isalignment is influenced by the social environment, the government, and the factors of secondary technical and vocational schools. However, optimizing professional programs and developing harmoniously with regional economies is a promising measure. On the other hand, strengthening the teaching staff's construction may be essential. Furthermore, it may provide more to promote the new development of secondary technical and vocational education in Wuxi City. Realizing the depth of high school cooperation, increasing investment in education, and improving the education award system and any others are under consideration.